Estrategias de neuroaprendizaje y el rendimiento académico de la asignatura de lengua y literatura en los alumnos de 7mo año educación básica de la unidad educativa “Quintiliano Sánchez Rendón” del cantón Buena Fe, periodo lectivo 2023 – 2024. - Santos Lara., Liseth Noralma (2024)
This development project investigates the impact of neurolearning strategies on the academic performance of 7th-grade students in the subject of Language and Literature. Faced with the challenge of improving educational outcomes in areas critical to cognitive and linguistic development, this research proposes an innovative approach focused on the application of neuroscientific principles. Through a mixed research design, levels of academic performance before and after the implementation of neurolearning strategies were evaluated. The findings suggest a significant relationship between the use of these strategies and improvement in performance in Language and Literature, offering empirical evidence that supports their integration into the educational curriculum. This study not only contributes to the pedagogical and neuroeducational field but also provides a practical framework for educators interested in effective neurolearning